Analisis Pengaruh Kependudukan dan Pendidikan Terhadap Pengangguran di Kabupaten Blitar Data Sakernas BPS 2022 - Rahmawati, Farida; Agus Saputri, Mega; Wahyuni, Lukhil; Masqurriah, Masqurriah (Rifa'Institute, 2023)
Unemployment is a problem that occurs in East Java, especially Blitar Regency. Several factors make the unemployment rate in Blitar Regency fluctuate, including population and education. According to some experts, every resident who enters the labor force but is unable to be absorbed or enters the workforce, this can lead to an increase in the unemployment rate. According to the educational factor, the higher a person's education, the higher the ability and opportunity to work. So that the government's efforts are needed to overcome this unemployment. The purpose of this research is to see the impact of education and population on unemployment in Blitar Regency. The method used is literature review (literature review). Based on the results of the study, it was concluded that the unemployment rate was contributed by residents with the highest educational level who graduated from elementary school, and the unemployment rate decreased by 0.16% from the previous year, from 3.82% to 3.66% of the total workforce of 657,544 residents. This is also influenced by the declining population growth rate and increasing awareness of education.